2010
DOI: 10.1037/a0017512
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in drinking motives mediate the relation between personality change and “maturing out” of problem drinking?

Abstract: Recent research has indicated that developmental changes in the personality traits of neuroticism and impulsivity correlate with changes in problem drinking during emerging and young adulthood. However, it remains unclear what potential mechanisms, or mediators, could account for these associations. Drinking motives, particularly drinking to regulate negative affect (drinking to cope) and to get "high" or "drunk" (drinking for enhancement) have been posited to mediate the relationship between personality and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
202
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(220 citation statements)
references
References 86 publications
12
202
1
5
Order By: Relevance
“…Our findings do not preclude the possibility that changes in more macro-level personality factors associated with regulating negative affect more directly influence (or are influenced by) AUD symptoms. For example, Littlefield et al (2010) found that long-term changes (between ages 18 and 35) in DTC motivation and AUD symptoms were both related to changes in the personality dimension of neuroticism (i.e., low emotional stability). Future research is needed to explicate how the processes we identified relate to longer-term developmental patterns linking emotional stability, DTC motivation, and AUD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings do not preclude the possibility that changes in more macro-level personality factors associated with regulating negative affect more directly influence (or are influenced by) AUD symptoms. For example, Littlefield et al (2010) found that long-term changes (between ages 18 and 35) in DTC motivation and AUD symptoms were both related to changes in the personality dimension of neuroticism (i.e., low emotional stability). Future research is needed to explicate how the processes we identified relate to longer-term developmental patterns linking emotional stability, DTC motivation, and AUD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Such variation in DTC motivation is consistent with Cooper andcolleagues' (1995, 2008) assertion that DTC is a reactive process, and thus DTC motivation should ebb and flow in response to life circumstances. Also, given previous theory and research linking DTC motivation with physiological and psychological dependence and withdrawal symptoms (e.g., Cooper et al, 1988;Littlefield et al, 2010;Merrill et al, 2014), we wanted to examine whether any observed association between changes in DTC motivation and the subsequent month's negative affect simply reflected relative levels of alcohol use disorder (AUD) symptoms. Thus, we first examined whether DTC motivation was associated with AUD symptoms and then examined whether the effect of DTC motivation on the subsequent month's affect was reduced when AUD symptoms were taken into account.…”
mentioning
confidence: 99%
“…Indeed, evidence from a longitudinal study of college students showed that changes in DTC motivation in young adulthood, but not changes in DTE motivation, correlated with changes in coping-relevant personality dimensions such as neuroticism and impulsivity (Littlefi eld et al, 2010). However, the mechanisms through which DTC motivation has these effects have been neither fully explicated nor examined in depth.…”
Section: Effects Of Drinking To Cope On Coping-relevant Resourcesmentioning
confidence: 99%
“…self-determination theory; Joussemet et al, 2008;Ryan and Deci, 2000). Moreover, recent research suggests that personality constructs, such as self-control, are infl uenced by environmental contexts such as parenting (e.g., Littlefi eld et al, 2010;Patock-Peckham et al, 2001. It is unknown whether this also holds true for the effects of alcohol-specifi c parenting on adolescent alcohol use (i.e., whether this effect is also mediated by the level of self-regulatory skills).…”
mentioning
confidence: 99%